Beyond Filmmaking: Searching for a Neorealist Architecture in Italy, 194X-195X. Issue 4 (19th May 2019) - Escudero, David
Abstract : After the Second World War, cinema was fundamental in portraying the spatial form of the time, while simultaneously contributing to the creation of a visual culture at a key moment in Italy. Despite the controversy regarding the definition of post-war cinematic style, Italian film of this time is generally globally recognised as 'neorealist'. Neorealist cinema created an environment that informed architecture, photography, painting, and other forms of art. The term neorealism has been adopted ad hoc in architecture, perhaps unconsciously, however the transfer has not been carefully studied. Placing the architecture-cinema relationship at the analytical focal point may shed light on some unaddressed questions: How did architecture get involved with cinematic discourse? What do the films and the architectural projects share? This article starts from the cultural context portrayed by films and investigates if and how — using which formal language, tools and references, and to what end — the neorealist discourse was transferred from film to architecture. Six projects are presented that help understand neorealist conditions in architecture: the Quartiere Tiburtino (Rome), La Martella village (Matera), the Towers in Viale Etiopia (Rome), the Quartiere in Cerignola (Foggia), the Quartiere San Basilio (Rome) and the Quartiere in Cesate (Milan).